Phytoestrogens and prostate cancer : experimental, clinical, and epidemiological studies - Bylund, Annika (Kirurgisk och perioperativ vetenskap, 2007)
Dietary factors may affect development and progression of prostate cancer. Experimental and epidemiological studies have suggested an effect of phytoestrogens on prostate cancer. Lignans are the predominant phytoestrogen in a Western diet. The effects of a diet rich in phytoestrogens and in particular lignans, as compared to a control diet, were assessed in several prostate cancer models. In paper I, 70 athymic nude mice with transplanted subcutaneous LNCaP tumours, an androgen sensitive human prostate cancer cell line, were fed one out of six phytoestrogen rich diets or a control diet after tumour injection. The rye diet, with high lignan content, decreased tumour take and growth, decreased secretion of prostate specific antigen and increased apoptosis. Addition of fat to the rye diet decreased the beneficial effects. In paper II, transgenic mice designed to develop prostate cancer (TRAMP) were fed rye bran or a control diet from the age of four weeks. Rye bran decreased prostate epithelial cell volume by 20%, and increased cell apoptosis by 31% as compared to the control diet. In paper III, we examined the effects of 7-hydroxymatairesinol (HMR), a purified lignan, in nude mice with subcutaneous LNCaP tumours in two different concentrations as compared to a control diet. Mice on the HMR diets had a reduced tumour take rate, lower total tumour volume, increased proportion of non-growing tumours, and increased apoptosis as compared to the control diet. Paper IV was a three week intervention study exploring the effects of rye bran bread vs. a control diet in men with prostate cancer. The men in the rye group had increased levels of plasma enterolactone and in biopsies from the prostate after the intervention an increase in apoptosis was observed in comparison with biopsies obtained before the intervention. In paper V, we examined the association between plasma levels of enterolactone, and risk of prostate cancer in a nested case control study. In the Northern Sweden Health and Disease Cohort, enterolactone ...